ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DALAM MENYELESAIKAN MASALAH KONTEKSTUAL HIMPUNAN - Cut Devy Nurfitriani; Abd Qohar (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
Mathematical connections are connecting mathematical concepts and mathematical concepts with other sciences and problems of everyday life. Mathematical contextual problems can be used to view and build students' mathematical connections. The purpose of this study was to describe how the mathematical connection abilities of junior high school students when solving contextual problems on set material. The type of research used is qualitative descriptive research. Research data obtained through mathematical connection tests and interviews. Analysis of mathematical connection ability is divided into modeling connections, concepts, representations, and procedures. The results of this study indicate that high mathematical ability students make modeling connections by making mathematical models, conceptual connections by connecting many members of each set, and procedural connections by operating algebraic forms correctly, representation connections are not carried out because students rarely use Venn diagrams. Students who are mathematically capable are not making modeling connections, concept connections, representation connections, and procedural connections. Students with low mathematical ability do not make modeling connections, concept connections, representation connections and procedural connections